Made by her vs. him: Gender influences in product preferences and the role of individual action efficacy in restoring social equalities - Benedikt Schnurr; Georgios Halkias (Journal of Consumer Psychology, 2022)
In response to the growing standardization and impersonalization of the market—side effects of new technology and business automation—consumers increasingly seek more personized purchase experiences, such as buying products directly from the producer. While extant literature has documented the positive effects of personizing market offerings, there is surprisingly little insight about whether knowing who made a product influences consumers' product preferences. We aim to fill this gap by focusing on the critical role of the producer's gender. In 13 studies, including field and online experiments (ntotal~=~2978), we observe a general preference for products made by women over products made by men, with female consumers consistently showing a strong preference for products made by women and male consumers showing no systematic preference for either product. We find that this difference between female and male consumers' product preferences occurs because female consumers, in relation to male consumers, hold stronger action efficacy beliefs—beliefs that their individual purchase choices can contribute to restoring gender equalities in business.
Keywords: 650; action efficacy; gender; personizing; product preference; social inequality